Propaganda i indoktrynacja w Ochotniczych Hufcach Pracy (1958–1983): wybrane problemy - Jackowski, Paweł (Polityka i Społeczeństwo, 2021)
Voluntary Work Camps were a Polish social organization, the aim of which was to engage youngsters in helping with the national economy of the Polish People’s Republic. Besides that, the main goal of the VWC was to conduct propaganda and indoctrinate the young people that participated. VWC’s propaganda was based on publishing materials such as ‘Biuletyn Informacyjny’ and cooperating with youth magazines. The most common technique used was to depict the idyllic everyday life of the VWC, where youngsters could, of course, earn money, but also learn a profession, make friends and enjoy the time that they spent in the camp. Young people were indoctrinated during the classes and lectures, which were often led by a professional propagandist. During the course of those lectures they were inculcated with the social vision of the world and they praised the achievements of the Polish People’s Republic. ‘Spartakiads’ were a particulary interesting way of indoctrination – these were sporting events thematically connected with the propaganda.